2008
DOI: 10.1590/s0102-76382008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Pressão venosa central em cateter femoral: correlação com acesso superior após cirurgia cardíaca

Abstract: The CVP can be measured with accuracy in the femoral venous approach in the immediate postoperative period of heart surgery with better linear correlation obtained with the measures made with the headboard positioned at zero degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Although both femoral sites were available, the reliability of femoral vein CVP readings as a surrogate is controversial, except when the intra-abdominal pressure is < 15 mmHg [ 2 ]. Pacheco et al [ 3 ] found a linear relationship between the superior vena cava and femoral vein readings when the head is positioned at zero degrees immediately after cardiac surgery. In contrast, a similar study by Groombridge et al [ 4 ] found poor agreement between the femoral and central venous pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Although both femoral sites were available, the reliability of femoral vein CVP readings as a surrogate is controversial, except when the intra-abdominal pressure is < 15 mmHg [ 2 ]. Pacheco et al [ 3 ] found a linear relationship between the superior vena cava and femoral vein readings when the head is positioned at zero degrees immediately after cardiac surgery. In contrast, a similar study by Groombridge et al [ 4 ] found poor agreement between the femoral and central venous pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Este ponto fica entre a linha axilar média e axilar anterior 4 . Outro ponto descrito para o eixo é na linha axilar média, no quarto ou quinto espaço intercostal; porém, importante lembrar que a utilização deste ponto pode superestimar a PVC real em até cinco mmHg 2,9,15 . A zeragem e o teste de resposta dinâmica devem ser realizados apenas quando em uso dos transdutores de pressão.…”
unclassified
“…± 4,6 mmHg (30 graus), mostrando não haver diferença significativa nas diferentes inclinações e inserções. A correlação linear entre as medidas nos dois sítios foi de 0,66 (zero grau) e 0,53 (30 graus), ambas com p < 0,0001 (PACHECO et al, 2008).…”
Section: 1unclassified